Extracting verb valency frames with Nooj - Šojat, Krešimir (Array, 2010)
The paper discusses the possibilities of describing verb valency on the basis of local grammars developed in the Nooj format. In this paper we use Nooj to describe the semantic and syntactic valency of app. 120 Croatian verbs belonging to the semantic field of consumation (e.g. eat, drink, devour, imbibe etc.).The whole semantic field, consisting of verbal lexical units is viewed as a single semantic frame. The approach relies on the theoretical background of frame semantics an is used in the development of the FrameNet. In such an approach the semantic valency of lexical units is described in terms of core and non-core elements characteristic for the whole frame. The level of syntax is observed as a level of realization or non-realization of conceptual arguments. As a starting point we use app. 40 sentence types consisting of morphosyntactic combinations possible in Croatian. For each sentence type a local grammar is built, with free word order taken into consideration. At the same time every lexical units is describeld in the Croatian Nooj dictionary. Each local grammar is applied to a corpus, and each occurence or non- occurences of lexical units in morphosyntactically annotated sentence types is analyzed. The obtained results show that certain verbs, although in terms of semantic valency all of them can intuitively be described as two argument verbs, are exclusively realized as one argument verbs on the syntactic level. Further results show the importance of non- core frame elements (e.g. means, company) for certain lexical units. The obtained results are further used for the refinement of verb frames in existing verb valency lexical of Croatian verbs and as a tool for distinguishing verb senses used in the development of the Croatian WordNet (CroWN).